Balancing prosperity and suffering theology: A theological approach to the reality of Christian life - Zebua, Lestan Iman; Rogate Artaida Tiarasi Gultom; Dapot Damanik (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study examines two contrasting theological approaches in modern church life, namely Prosperity Theology and Suffering Theology. Prosperity Theology emphasizes faith as a path to health, wealth, and success, while Suffering Theology sees suffering as a means of forming faith and Christlikeness. Using a qualitative method based on literature study, this study evaluates the teachings of both approaches based on biblical sources, classical and contemporary literature, and church ministry practices in Indonesia. The results of the analysis show that an imbalance in understanding these two approaches can lead to deviations in the life of faith. Therefore, an integrative theological approach is needed, which recognizes blessings and suffering as part of God's work in shaping the lives of believers. This study recommends that churches and theological educational institutions pay balanced attention to the teachings on blessings and suffering in order to produce healthy and contextual ministries.